Teachers’ Perceptions of Students’ Numeracy Competency Measured by Using the Minimum Competency Assessment - Susanto, Edi; Mahmudi, Ali (Kreano, Jurnal Matematika Kreatif-Inovatif, 2024)
Teachers have positive perceptions about the implementation of the Minimum Competency Assessment (MCA) and reading literacy. However, mathematics teachers also need to have a perception of students' numeracy skills that are assessed using the MCA instrument. Teachers experience various challenges and difficulties in improving learning to strengthen numeracy. This study aims to describe teachers' perceptions of students' numeracy competencies measured using MCA and to identify efforts made by teachers to strengthen students' numeracy competencies. This type of research is descriptive research with a qualitative approach. The results of this study indicate that teachers' perceptions of students' numeracy competence measured using the MCA instrument are positive (agree) so that teachers can make appropriate efforts in improving the quality of learning and strengthening numeracy. The efforts that teachers can make are looking for information on achievement results, reading report card data, identifying the root of the problem, and fixing the problem. Positive teacher perceptions encourage teachers to make appropriate efforts in strengthening students' numeracy competencies and support schools to develop data-based programs. Guru memiliki persepsi positif tentang pelaksanaan Asesmen Kompetensi Minimum (MCA) dan literasi membaca. Namun, guru matematika juga perlu memiliki persepsi tentang kemampuan numerasi siswa yang dinilai menggunakan instrumen MCA. Guru mengalami berbagai tantangan dan kesulitan dalam memperbaiki pembelajaran untuk menguatkan numerasi. Penelitian ini bertujuan untuk mendeskripsikan persepsi guru tentang kompetensi numerasi siswa yang diukur menggunakan MCA dan untuk mengidentifikasi upaya yang dilakukan oleh guru sebagai penguatan kompetensi numerasi siswa. Jenis penelitian ini merupakan penelitian deskriptif dengan pendekatan kualitatif. Hasil penelitian ini menunjukkan bahwa persepsi guru tentang kompetensi numerasi siswa yang diukur menggunakan instrumen MCA adalah positif (setuju) sehingga guru dapat melakukan upaya yang tepat dalam memperbaiki kualitas pembelajaran dan melakukan penguatan numerasi. Adapun upaya yang guru dapat lakukan adalah mencari informasi hasil capaian, membaca data rapor pendidikan, mengidentifikasi akar permasalahan, dan membenahi masalah. Persepsi guru yang positif mendorong guru agar dapat melakukan upaya yang tepat dalam menguatkan kompetensi numerasi siswa dan mendukung sekolah menyusun program berdasarkan data.